Valorisation of lignocellulosic biomass with ionic liquids in the frame of green chemistry and biorefinery concepts - Lopes, André Miguel da Costa (2017)
The current need to move from a fossil-derived economy to sustainable bio-based and circular economy is highly demanding. The utilisation of lignocellulosic biomass, as a renewable carbon source, for the production of fuels, chemicals and materials is a promising solution that has been widely explored in recent years. In this framework, the present thesis discloses the development of novel technologies using ionic liquids (ILs) for biomass valorisation following the green chemistry and biorefinery concepts. Two different approaches, on the basis of the chemical character of examined ILs, i.e. acidity and basicity, paved the way for a fractionation of wheat straw into main components, namely cellulose, hemicellulose and lignin, either in their polymeric or hydrolysed forms. A first strategy relied on the development of a three-step fractionation process using alkaline 1-ethyl-3-methyimidazolim acetate ([emim][OAc]) allowing selective separation of cellulose, hemicellulose and lignin as high purity fractions. The recovered IL demonstrated the presence of soluble phenolic compounds, which were extracted and purified by means of polymeric resin and supercritical CO2 extraction methods. The second strategy integrated a pre-treatment, hydrolysis and conversion of biomass in a single step process through the employment of acidic imidazolium ILs containing HSO4 anion. These ILs revealed the ability to selectively hydrolyse and convert the hemicellulosic fraction of wheat straw into pentoses and/or furfural, in which the formation of pentoses are favoured in presence of water. The resulting solid composed mainly of cellulose and lignin was fractionated and processed towards the production of glucose, highly pure lignin and also phenolic compounds. Both types of ILs were recovered and reused without losing their performances in biomass valorisation, showcasing efficient and sustainable processes for implementation in biorefineries.